A Glaucoma-Specific Brief Motivational Interviewing Training Program for Ophthalmology Para-professionals: Assessment of Feasibility and Initial Patient Impact. Issue 2 (28th January 2020) - Newman-Casey, Paula Anne; Killeen, Olivia; Miller, Sarah; MacKenzie, Chamisa; Niziol, Leslie M.; Resnicow, Ken; Creswell, John W.; Cook, Paul; Heisler, Michele
ABSTRACT: Our objective was to test the feasibility of, fidelity to, and initial impact of a brief, glaucoma-specific motivational interviewing (MI) training program for ophthalmic para-professionals. This prospective, mixed-methods study had two components, one for staff and one for patients. Staff fidelity to MI principles was graded through audio-recorded encounters after initial and final training sessions. After training, patients graded staff for adherence to autonomy supportive care. Semi-structured interviews with para-professionals elicited feedback about the training and about their ability to implement MI in the clinic. The impact on patient satisfaction with staff communication, eye drop instillation self-efficacy, and overall health activation was assessed using a survey pre- and post-training. Para-professionals met two of three program goals for MI skills and improved in their overall scores for MI fidelity. Para-professionals noted lack of time in the clinic as a significant barrier to implementing counseling. Patient satisfaction with staff communication increased after the training ( p = 0.04) among patients who rated their staff above the mean for providing autonomy supportive care. The intervention did not improve patients' eye drop instillation self-efficacy or overall health activation. Training para-professional staff in brief, glaucoma-specific MI techniques is feasible and may improve patient satisfaction, though dedicated time in clinic is needed to implement MI counseling into glaucoma practice.